PLAY ACTIVITIES IN THE PROCESS OF EMOTIONAL AND INTELLECTUAL DEVELOPMENT OF PRESCHOOL CHILDREN (Multidisciplinary Journal of Science and Technology, 2025)
This article explores the crucial role of play activities in shaping the emotional and intellectual development of preschool children. Play is regarded not merely as entertainment but as an essential medium through which children learn, communicate, and construct their understanding of the world. The study emphasizes how different types of play — symbolic, constructive, social, and cognitive — contribute to developing empathy, creativity, problem-solving skills, and emotional regulation. Attention is given to the pedagogical role of teachers and parents in organizing play environments that stimulate curiosity and self-expression. The paper concludes that structured yet flexible play is one of the most powerful instruments in nurturing a child’s holistic growth and readiness for school life.